Dalbavancin in the treatment of acute bacterial skin and skin structure and other infections: a safety evaluation. Issue 9 (2nd September 2022) - Righi, Elda; Visentin, Alessandro; Meroi, Marco; Carrara, Elena; Tacconelli, Evelina
ABSTRACT: Introduction: Dalbavancin is a second-generation lipoglycopeptide approved since 2014 to treat acute bacterial skin and skin-structure infections (ABSSSI). Dalbavancin is characterized by Gram-positive activity and novel pharmacokinetic properties allowing prolonged terminal half-life andonce weekly dosing . A good safety profile was reported in clinical trials . Areas covered: Dalbavancin safety and tolerability from trials and post-marketing studies were reviewed. While most reports included predominantly ABSSSI, two clinical trials and recent observational studies have explored the use of dalbavancin for off-label indications, mainly including bloodstream and osteoarticular infections. Expert opinion: The occurrence of drug-related adverse effects (AE) was similar between dalbavancin and comparators in clinical trials enrolling patients with ABSSSI. Most common AE included gastrointestinal symptoms, infusion reaction, and hypersensitivity. Low rates of drug discontinuation and serious AE were reported across studies. In the past 5 years, several observational studies have reported safety data on the use of dalbavancin, confirming its favorable safety profile. Nevertheless, data from dalbavancin off-label use, often derived from prolonged (>2 weeks) treatments with variable dosing regimens, were mainly retrospective and lacked comparators. Further research is required to allow a reliable analysis of short- and long-term dalbavancin-related AE in non-ABSSSI.